New Records of Mosquito Species in the Province of Formosa, Northeastern Region of Argentina - Hoyos, Carlos Blas (2011)
Six species are recorded for the 1st time in Formosa province, northeast region of Argentina: Culex delpontei, Cx. eduardoi, Cx. educator, Cx. maxi, Cx. pilosus, and Toxorhynchites theobaldi, increasing the number of species of that province to 73.